The effects of after-school programs on maternal employment - Fabian Dehos; Marie Paul (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This paper evaluates the impact of a massive expansion of after-school programs (ASPs) on the labor market participation of mothers with primary school children in the West German context of relatively low full-time employment rates. Using an instrumental variables approach we exploit regional and temporal variation in the provision of federal ASP starting grants by a nationwide investment program. Results suggest that additional ASP places had no effect on working hours or the employment probability of mothers with primary school children. – – Das vorliegende Diskussionspapier untersucht den Einfluss einer massiven Ausweitung von Ganztagsbetreuung an Grundschulen auf das Arbeitsangebot von Müttern im westdeutschen Kontext einer niedrigen Vollzeitbeschäftigungsquote. Wir verwenden einen Instrumentvariablenansatz und nutzen zur Identifikation des Effektes regionale und zeitliche Variation in der Zuteilung von Fördergeldern eines bundesweiten Investitionsprogramms. Unsere Ergebnisse zeigen, dass die zusätzlichen Ganztagsschulplätze weder einen Einfluss auf die Anzahl der geleisteten Arbeitsstunden noch auf die Beschäftigungswahrscheinlichkeit von Müttern mit Grundschulkindern haben.
Keywords: J13; J21; J22; 330; Maternal employment; after-school programs; instrumental variables